2021
DOI: 10.1002/er.6364
|View full text |Cite|
|
Sign up to set email alerts
|

A hybrid disassembly framework for disassembly of electric vehicle batteries

Abstract: In a recent study, it was determined that the usage of Li-Ion batteries in electric vehicles (EVs) represent a huge portion of the overall usage. In order to foster a sustainable future, Li-Ion batteries in EVs generally undergo a disassembly during the recycling process, which is intended for secondary purposes or recover useful materials and components. However, the current disassembly process is significantly time consuming and expensive. Hence in this research, a disassembly framework is presented, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…[196,285] There are several publications discussing the automation potential of battery disassembly. [285][286][287][288] For instance, Hellmuth et al identified a 46-step disassembly sequence for a 2017 Chevrolet Bolt battery and found that about one-third of the steps could be automated based on an assessment of the technical feasibility and necessity of automation. At present, fully automated disassembly by self-learning robots remains unrealistic due to the high complexity of some disassembly steps.…”
Section: Design For Recyclingmentioning
confidence: 99%
“…[196,285] There are several publications discussing the automation potential of battery disassembly. [285][286][287][288] For instance, Hellmuth et al identified a 46-step disassembly sequence for a 2017 Chevrolet Bolt battery and found that about one-third of the steps could be automated based on an assessment of the technical feasibility and necessity of automation. At present, fully automated disassembly by self-learning robots remains unrealistic due to the high complexity of some disassembly steps.…”
Section: Design For Recyclingmentioning
confidence: 99%
“…Current pack disassembly is complex but technoeconomic analysis shows how disassembly could be possible [115]. Hybrid disassembly protocols have also been suggested [116].…”
Section: Statusmentioning
confidence: 99%
“…그 럼에도 폐배터리의 잔존 에너지로 인해 단락 등 급격한 방 전이 발생할 경우 감전 및 열폭주(thermal runaway) 등의 안전위험이 존재한다 5,35) . 열폭주는 그 자체도 문제지만 그 로 인해 배터리내 함유된 플라스틱, 바인더(polyvinylidene fluoride) 및 LiPF6(salt lithium hexafluorophosphate) 등 이 연소되어 메탄, 에탄, 프로판 등의 휘발성 가스 및 일산 화탄소 및 불산(HF) 같은 독성(noxious or carcinogenic) 가스가 발생되면, 작업자 안전 및 환경을 위협할 수 있다는 점도 유의할 문제이다 5,35,39) . 또한, 배터리내 불소화합물은 물과 접촉 시 환경과 인체 및 생태계의 건강에 또 다른 형 태의 악영향을 미칠 수 있다 5,39) .…”
Section: 안정화 이후에도 기술측면에서 안전하고 신속한 해체unclassified